(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The aim of this research was to answer the question about whether there is a difference regarding the professional burnout, the sources of stress and life’s pleasure among the teachers working in the secondary schools in RM associated with the place of work, the sex and the length of service. The specimen includes 440 educational workers, out of which 220 are from the secondary schools in the interior of the RM and 220 are from the secondary schools in Skopje. The research was carried out in the period between February and April 2018. The results show that there is not a statistically significant difference in the level of manifestation of the professional burnout, the sources of stress and life’s pleasure between the teachers working in the interior secondary schools in RM and the ones working in Skopje. The research has shown that the age and length of service considerably correlate with the professional burnout and the level of experienced stress, whereby the older group with the longest length of service is the most susceptible to the influence of the professional burnout and the sources of stress in the teachers.